In Search of Humble Leaders - Bergen, C.W. Von; Bressler, Martin S. (The Institute of Academic Research and Publication (IARP), 2022)
The significance of moderation and balance across various domains has been sanctioned for millennia and deviations from midpoints of virtues, traits, qualities, and other attributes have been described as dysfunctional suggesting a nonmonotonic, U-shaped curve. Modern scholarship and lay interpretations of the virtue of humility have neglected this perspective and appear to tacitly assume that humility is an unmitigated good that leaders should develop and that more is better. Here we show, however, that what we refer to as authentic humility, is positioned at an intermediate point between negative and positive views of the self and that deviations from this center adversely impact well-being and offer a nonlinear, inverted U-shaped curve. Such an interpretation reconciles views of humility as a weakness or strength and demonstrates its positive impact on self, followers, and organizational well-being. We conclude by suggesting that humility has costs for leaders and therefore not an unmitigated good.